Study of some molecular biological characteristics of three 2,4-D degrading bacterial strains isolated from herbicide/dioxin contaminated soil in Da Nang - Huu, Nguyen Ba; Cam Ha, Dang Thi (Academia Journal of Biology, 2014)
Three 2,4-dichlorophenoxyacetic acid (2,4-D) degrading bacterial strains DNB19, DNB20 and DNB21 isolated from herbicide/dioxin contaminated soil in former military base in Danang were compared by BOX-PCR fingerprint technique and sequence analysis a part of 16S rRNA gene. Although there are few differences on conoly morphology, three these strains are identity on sequence 16S rRNA gene (550 bp) as well as ADN patterns of BOX-PCR products. The result of sequence analysis of 16S rRNA genes shown that three strains DNB19, DNB20 and DNB21 had high similar to bacterial strains in genus Arthrobacter. Based on the morphological features and 16S rRNA sequence analysis, three strains DNB19, DNB20 and DNB21 should be belong to genus Arthrobacter and named as Arthrobacter sp. DNB19, Arthrobacter sp. DNB20 and Arthrobacter sp. DNB21. The strain DNB19 was selected to study the present of cadA and tfdA genes involved in the first step of 2,4-D degradation pathways. The sequence of a part of cadA and CadA hypotherical amino acid in DNB19 shown highest levels to cadA (93%) and CadA (97%) from Sphingomonas sp. B6-10. The sequence of a part of tfdA and TfdA hypotherical amino acid in DNB19 shown highest levels to tfdA (94%) from Burkholderia sp. RASC, Burkholderia sp. Ff54, Ralstonia sp. Y103 and TfdA from Burkholderia sp. RASC (96%), Delftia acidovorans P4a (95%). The sequence of CadA hypotherical amino acid in DNB19 also shown similarlity 48% to TftA from 2,4,5-T degrading bacterium Burkholderia cepacia AC1100.